IMPACT OF DIGITAL FORMATION ON SMALL AND MEDIUM ENTERPRISES (SMES): CHALLENGES AND OPPORTUNITIES - T Ramesh, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Digital transformation (DT) has become a serious factor for businesses worldwide, enabling them to enhance operational efficiency, improve customer engagement, and gain an inexpensive edge. However, for Small and Medium Enterprises (SMEs), the journey of adopting and integrating digital technologies often remains fraught with challenges. This research investigates the impact of digital transformation on SMEs by employing a mixed-methods approach. A combination of qualitative interviews with SME owners and managers and quantitative surveys across a larger sample of SMEs provides a complete understanding of the drivers, blocks, and outcomes of digital implementation. The study explores the inspirations behind digital transformation, the challenges faced during the implementation process, and the apparent benefits SMEs derive from implementing digital technologies. Results indicate that while SMEs face resource constraints and resistance to change, digital change leads to significant improvements in operational efficiency, market expansion, and customer satisfaction. The findings offer helpful details about the strategies SMEs can adopt to navigate the digital transformation process successfully. This research contributes to the growing body of information on digital transformation in SMEs and offers practical recommendations for businesses looking to enhance their digital capabilities.